ZINCO EM ALGUNS SOLOS DE PIRACICABA â€“ AVALIAÃ‡ÃƒO POR TESTES QUÃMICOS - Sobrinho, M. O. Camponez do Brasil; Freire, O.; Silveira, R. I. (REVISTA DE AGRICULTURA, 2020)
ZINCO EM ALGUNS SOLOS DE PIRACICABA â€“ AVALIAÃ‡ÃƒO POR TESTES QUÃMICOS